The Effect of Compensation on Employee Performance with Work Motivation as Intervening Variable - Fendik, Zhafirah Utami; Hakim, Lukman (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Objective: Knowing the direct relationship between compensation and performance, as well as the mediating role of work motivation factors in the relationship between compensation and performance. Methodology: This study used quantitative research methods with explanatory research. The data collected is in the form of questionnaires and documents from government institutions. Test the hypothesis in this study using a path analysis model, while for the mediation test, researchers manage the data using the Sobel Test. The population used was employees of the Government of Environmental Office in Surakarta City who worked in the field, a research sample of 30 respondents with proportional random sampling as a sampling technique. Results: According to study using path analysis testing, employee performance is not significantly impacted by compensation variables. Subsequently, the outcomes of utilizing the Sobel Test and the Sobel Calculator to assess work motivation as an intervening variable demonstrated that work motivation acts as a mediator between the impact of compensation and employee performance. Employee performance is unaffected by an employee's higher pay. Nonetheless, the influence of remuneration on worker performance may involve an intermediary factor: the supply of motivation. Application / Originality / Value: Based on several existing research, there has yet to be any research that discusses the topics and objects of research that were researched in this research. The underlying difference with previous research is that this research used a population of employee respondents who worked in the field, not in an administrative environment. The novelty of this study is that respondents are the employees who worked in the field, while previous research used respondents on employees who worked in the administrative sphere.